2017
DOI: 10.1186/s10194-017-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient sleep is prevalent among migraineurs: a population-based study

Abstract: BackgroundSleep disorder and sleep complaints are common in subjects with migraine. Although the association between sleep disorders and migraine has been reported, the association between perceived insufficient sleep and migraine has rarely reported. The aim of this study is to evaluate the association between insufficient sleep and migraine using the data of the Korean Headache-Sleep Study (KHSS).MethodsThe KHSS is a nation-wide cross-sectional population-based survey regarding headache and sleep for Korean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 32 publications
3
54
0
Order By: Relevance
“…5,14 Patients with migraine report increased insomnia complaints interictally -including difficulty initiating sleep, staying asleep, poor sleep quality, self-reported decreased total sleep time, excessive daytime sleepiness, and lack of refreshment after sleep. [15][16][17][18][19][20][21][22][23][24][25] Such findings persist when controlling for comorbid anxiety and depression. 23 These frequent subjective complaints of insomnia among persons with migraine have also led to the notion that poor sleep may be a part of the migraine endophenotype.…”
Section: Sleep Disorders and Their Relationship To Migrainementioning
confidence: 86%
See 1 more Smart Citation
“…5,14 Patients with migraine report increased insomnia complaints interictally -including difficulty initiating sleep, staying asleep, poor sleep quality, self-reported decreased total sleep time, excessive daytime sleepiness, and lack of refreshment after sleep. [15][16][17][18][19][20][21][22][23][24][25] Such findings persist when controlling for comorbid anxiety and depression. 23 These frequent subjective complaints of insomnia among persons with migraine have also led to the notion that poor sleep may be a part of the migraine endophenotype.…”
Section: Sleep Disorders and Their Relationship To Migrainementioning
confidence: 86%
“…1525 Such findings persist when controlling for comorbid anxiety and depression. 23 These frequent subjective complaints of insomnia among persons with migraine have also led to the notion that poor sleep may be a part of the migraine endophenotype. To this end, several studies have examined the baseline polysomnography data of patients with migraine.…”
Section: Sleep Disorders and Their Relationship To Migrainementioning
confidence: 99%
“…46 Most recently, it has been demonstrated that poor sleep quality may mediate sensitivity to lack of sleep as a headache trigger in people with headache, including migraine headache. 49 Although poor sleep quality, as measured by the Pittsburgh Sleep Quality Index, in those with migraine is a common finding, 45,4749 not all studies have found increased daytime somnolence. 47 Others, however, have reported excessive daytime sleepiness to be 3-fold more likely in those with migraine 44 and 4-fold more likely in those with CM 50 than in those without headache.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors include age, socioeconomic status, obesity, adverse childhood experiences, stressful life events in adulthood, depression, overuse of acute medications, ineffective acute medications, and possibly caffeine use. [6][7][8][9] The relationship is complex since sleep disturbances may trigger a migraine attack, 10 while adequate sleep can be protective against migraine attacks, 11 and many patients use sleep to abort individual attacks. [3][4][5] Migraineurs frequently report poor sleep quality, which is associated with increased migraine frequency and severity.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Migraineurs frequently report poor sleep quality, which is associated with increased migraine frequency and severity. [6][7][8][9] The relationship is complex since sleep disturbances may trigger a migraine attack, 10 while adequate sleep can be protective against migraine attacks, 11 and many patients use sleep to abort individual attacks. A recent study reported that patients with insomnia had a higher prevalence of migraine than did patients without insomnia; interestingly, patients with migraine who had insomnia reported more headache-related disability (as measured by the Headache Impact Test [HIT-6]) than patients with migraine but without insomnia.…”
Section: Introductionmentioning
confidence: 99%